1996
DOI: 10.1002/(sici)1096-9063(199611)48:3<225::aid-ps462>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Flow Pathways and Their Capacity to Transport Isoproturon in a Structured Clay Soil

Abstract: A field experiment was established to monitor preferential flow pathways and their capacity to transport isoproturon in a heavy clay soil. A hydrologically defined plot of 600 m2 at a field site on the Oxford University Farm at Wytham was created with integral flow monitoring and sampling devices. Data are presented from two flow events which occurred in April and May 1994. The highest concentrations of isoproturon (130 pg litre-') were observed in the drainage system. The vast majority of the 0.7% of applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(12 citation statements)
references
References 13 publications
(6 reference statements)
1
11
0
Order By: Relevance
“…Several previous studies have observed preferential flow mechanisms operating in soils (Harris et al, 1994;Johnson et al, 1996) and this is appears to be occurring at this site. Rainfall data (Figure 4) shows heavy precipitation in the days just before the major pulse of diuron and its metabolites migrate more rapidly through the soil after 36 days.…”
Section: Discussionmentioning
confidence: 51%
“…Several previous studies have observed preferential flow mechanisms operating in soils (Harris et al, 1994;Johnson et al, 1996) and this is appears to be occurring at this site. Rainfall data (Figure 4) shows heavy precipitation in the days just before the major pulse of diuron and its metabolites migrate more rapidly through the soil after 36 days.…”
Section: Discussionmentioning
confidence: 51%
“…most clay soils in the UK) frequently experience problems because pesticides can be transported via preferential flow pathways to field drains (e.g. Gärdenäs et al, 2006;Haria et al, 1994;Harris and Catt, 1999;Harris et al, 1994;Jarvis, 2007;Johnson et al, 1996;Köhne et al, 2009;Larsson and Jarvis, 1999). One example is provided by the Upper Cherwell catchment (1°14′W, 52°12′ N; area 176 km 2 : May et al, 2001) which is a tributary of the River Thames (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Other investigations have been concerned with individual small plots which contain one or two tile drains; monitoring usually includes the quantity and quality of outflows from tile drains due to pesticide leaching. In one field study (Johnson et al, 1996), isoproturon was applied to a tile-drained field of winter wheat, the first drain flow following pesticide application reached a maximum discharge within 3 h and the maximum pesticide concentration occurred 30 min later. Further examples of detailed field investigations are presented by Richard and Steerhuis (1988), Haria et al (1994), McVoy et al (1995), Harris and Catt (1999), Villholth et al (2000), Gerke and Köhne (2004), Gärdenäs et al (2006) and Stone and Wilson (2006); apart from the investigation of Gärdenäs et al (2006), the studies relate to areas of less than 1 ha with ground slopes less than 3%.…”
Section: Introductionmentioning
confidence: 99%
“…We know little about the mechanisms of lateral pesticide transport. Johnson et al (1996) studied the relative importance of surface‐, lateral subsurface‐, and drainage transport of isoproturon [3‐(4‐isopropylphenyl)‐1,1‐dimethyluree] in a moderately sloped clay soil in Oxford, UK, during two major rain events. They stated that 23% of a total recovery of 0.7% of mass was transported with lateral subsurface flow.…”
mentioning
confidence: 99%